Pengaruh Penerapan Model Pembelajaran Cooperative Learning Tipe Group Investigation terhadap Hasil Belajar Siswa Kelas VIII di SMP Negeri 1 Banjar - Naibaho, Birgita Rani Estika; Luh Indrayani; Ni Wayan Ayu Santi (Universitas Pendidikan Ganesha, 2025)
This study aims to assess the impact of the Group Investigation (GI) learning model on student outcomes in Social Sciences. The research employs a quasi-experimental design with a nonequivalent control group, also known as the two-group pretest-posttest design. The population of this study includes students from SMP Negeri 1 Banjar, totaling 372 students. Sampling was conducted using simple random sampling. The sample consists of class VIIIA1 as the experimental group and class VIIIA2 as the control group. Data collection utilized pretest and posttest with multiple-choice questions. The analysis methods employed are descriptive statistics and t-tests. The results indicate that the average score for the experimental group was 53.28 with a completion rate of 9.38% on the pretest, which increased to an average score of 81.88 with a completion rate of 93.75% on the posttest. For the control group, the average score initially was 53.59 with a completion rate of 6.25% on the pretest, and improved to an average score of 73.91 with a completion rate of 81.25% on the posttest. It is evident that the experimental group achieved higher scores compared to the control group following the implementation of the Group Investigation cooperative learning model. Based on these findings, it can be concluded that the Group Investigation cooperative learning model positively affects student outcomes in Social Sciences.